Estudio De Cartera Vencida Y Su Efecto En La Liquidez De La Cooperativa De Ahorro Y Credito Vinces Ltda - Camacho Veas, Roger Alfredo (2017)
he present case study is framed in the research sub-line of the career of commercial engineering that is the model of administrative management in relation to the study of past due portfolios and its effect on the liquidity of the Cooperative Vinces Ltda. is dedicated to the activities of saving and credit giving to the partners the opportunity to save their money and also making loans to those who need for their investment or consumption.